Brief: Fabrication Processes Of Silicon-On- Insulator And Lateral Bipolar Transistors - S Hamad, Osama; Sidek, Othman; Rehman, Mahfoozur; Ibrahim, Kamarulazizi (2008)

(untitled)
Silicon on Insulator (SOI) has long been the forerunner of the CMOS technology in the last decade offering superior CMOS with higher speed, higher density, and excellent radiation hardness and reduced second order effects for submicron VLSI applications.